Efektivitas Three Finger Grip Dengan Four Finger Grip Terhadap Akurasi Sidehand Throw Posisi Infield Olahraga Softball - Dwi Irawan (Journal of Physical Activity and Sports (JPAS), 2020)
The background of this research is that players often make mistakes when throwing a side throw at the Infield position. The formulation of the research problem is which is more effective using Three Finger Grips with Four Finger Grips to the accuracy of Sidehand Throw at the Infield position in Softball, Softball Team, Universitas PGRI Semarang 2020. The purpose of this study is to see the effectiveness of the throws using Three Finger Grips with Four Finger Grip on the accuracy of the Sidehand Throw at the Infield position in Softball, the Softball Team of the PGRI University Semarang 2020. In this research, to collecting the data is using a descriptive method. The technique of analysis is using a significant similarity test for two means (one party). In this study, the samples used 13 male students of the softball team Universitas PGRI Semarang 2020 with the saturated sampling technique. The mean of three fingers is 22, the standard deviation (Std.Deviation) is 3.78, the minimum and maximum of values are 18 and 30, the mean of four fingers is 26, the standard deviation (Std. Deviation) is 4.89, minimum and maximum of values are 20 and 34. The results of the calculation obtained the value of thitung (2,086) > ttabel (1,70) so that H0 is rejected, which can be concluded that the four-finger grip is more effective than three-finger grips on sidehand accuracy throw at the infield position in the softball team of Universitas PGRI Semarang 2020. The conclusion using a three-finger grip on the accuracy of the sidehand throw at the infield position in the softball team Universitas PGRI Semarang 2020 are categorized as effective. While the results of the throw using four-finger grips on the accuracy of sidehand throws at the infield position in the softball team Universitas PGRI Semarang 2020 are categorized as effective. The four-finger grip is more effective than the three-finger grip on the accuracy of sidehand throws at the infield position in the softball team Universitas PGRI Semarang 2020. It is hoped that athletes can use the four-finger grip because it is more effective for the accuracy of sidehand throws at the infield position in softball.   Keywords: Three Fingers, Four Fingers, Sidehand Throw Infield Softball. Latar belakang  dari penelitian ini adalah pemain sering melakukan kesalahan saat melakukan lemparan samping pada posisi infield. Rumusan masalah penelitian ini yaitu manakah yang lebih efektif menggunakan Three Finger Grip dengan Four Finger Grip terhadap akurasi Sidehand Throw pada posisi Infield dalam olahraga Softball tim Softball Universitas PGRI Semarang 2020. Tujuan penelitian ini yaitu untuk mengetahui efektivitas hasil lemparan dengan menggunakan Three Finger Grip dengan Four Finger Grip terhadap akurasi Sidehand Throw pada posisi Infield dalam olahraga Softball tim Softball Universitas PGRI Semarang 2020. Pengumpulan data penelitian ini menggunakan metode deskritif. Teknik analisis yang dipakai menggunakan uji signifikan kesamaan dua rata-rata(satu pihak). Pada penelitian ini sampel yang digunakan sebanyak 13 mahasiswa putra tim softball Universitas PGRI Semarang dengan teknik Sampling Jenuh.  Hasil rata-rata(mean) three fingers sebesar 22, Simpangan baku (Std.Deviation) sebesar 3,78, nilai minimum dan maksimum sebesar 18 dan 30, Hasil rata-rata(mean) four fingers sebesar 26, Simpangan baku (Std.Deviation) sebesar 4,89, nilai minimum dan maksimum sebesar 20 dan 34. Hasil perhitungan diperoleh nilai thitung (2,086) > ttabel (1,70) sehingga H0 ditolak yang dapat disimpulkan bahwa Four finger grip lebih efektif dibandingkan three finger grip terhadap akurasi sidehand throw pada posisi infield dalam olahraga softball tim softball Universitas PGRI Semarang 2020. Kesimpulannya adalah bahwa hasil lemparan menggunakan three finger grip terhadap akurasi sidehand throw pada posisi infield dalam olahraga softball tim softball Universitas PGRI Semarang 2020 berkategori efektif. Sedangkan hasil lemparan menggunakan four finger grip terhadap akurasi sidehand throw pada posisi infield dalam olahraga softball tim softball Universitas PGRI Semarang 2020 berkategori efektif. Hasil Perbandingan four finger grip lebih efektif daripada three finger grip terhadap akurasi sidehand throw pada posisi infield dalam olahraga softball tim softball Universitas PGRI Semarang 2020. Diharapkan bagi atlet dapat menggunakan  four finger grip karena lebih efektif terhadap akurasi sidehand throw pada posisi infield dalam cabang olahraga softball.   Kata kunci: Tiga jari, empat jari, lemparan samping infield softball